WORKSHOPS IN COGNITIVE PROCESSES - BENNETT A.; HOUSFELD S. REEVE R.A. AND SMITH J. (ROUTLEDGE & KEGAN PAUL, LONDON, 1981)
This book is designed as a text for undergraduate courses in psychology and extensively revised and expanded for this edition, this practical manual gives students the opportunity to find out for themselves about some cognitive processes. It aims at student involvement and discussion and encourages experiment and investigation.
Keywords: CHILD AND ADOLESCENT DEVELOPMENT